Capaian Warna Tinta Berbahan Dasar Pigmen Organik terhadap Tinta Acuan Cetak Saring Konvensional - Galang Aryo Jati; Rachmah Nanda Kartika; Heribertus Rudi Kusumantoro (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
This study aims to evaluate the color of organic ink based on coffee grounds charcoal as an alternative to conventional ink in screen printing. The experimental method was conducted with three variations of pigment formulation and distilled water, namely: 15 gr & 41 ml, 20 gr & 45 ml, 25 gr & 49 ml). Testing of solid content levels and Lab values was carried out to determine color characteristics, as well as delta E calculations to compare with conventional inks. The results showed the highest solid content in the 20 g formulation, but the 15 g ink distribution produced the closest color to the reference ink due to better flow. In conclusion, proper material formulation is essential to achieve optimal color quality.